Malignant hyperthermia in Lesch-Nyhan disease - William L Nyhan; Michelle Lucas (Archives of Clinical Nephrology - Peertechz Publications, 2019)
Lesch-Nyhan disease is a heritable disorder of purine metabolism. Inheritance is X-linked and the disease occurs almost exclusively in males. Defective activity of hypoxanthine phosphoribosyltransferase leads to hyperuricemia and increased quantities of uric acid in the urine. All patients may develop urinary calculi, urate nephropathy, tophaceous deposits and clinical gout. Neurologic disability and abnormal aggressive behavior is characteristically self-injurious.  We report 2 patients with this disease who have been observed to have multiple episodes of hyperthermia which appear to fit the definition of malignant hyperthermia.